The capability of organic compounds to swell acrylonitrile butadiene O-rings and their effects on O-ring mechanical properties. (15th February 2019) - Romanczyk, Mark; Ramirez Velasco, Jorge H.; Xu, Lan; Vozka, Petr; Dissanayake, Pankaja; Wehde, Katherine E.; Roe, Nathaniel; Keating, Eion; Kilaz, Gozdem; Trice, Rodney W.; Luning Prak, Dianne J.; Kenttӓmaa, Hilkka
Abstract: As interest in replacing petroleum-derived aviation fuels with resilient, alternative fuels increases, the ability to derive correlations between the chemical compositions of aviation fuels and their properties and performance becomes more important. In this work, correlations between the exact chemical structures of organic compounds and their ability to increase the volume and decrease the tensile strength of Buna-N o-ring seals were explored. Buna-N o-ring seals are a representative group of essential seals in the hydraulic and pneumatic components of aircraft fuel delivery systems. They are utilized to prevent fuel leakage within the pumps, metering devices, and connectors. To measure the volume swell percent of o-ring seals caused by various organic compounds, a test rig was assembled that suspended o-ring seals in neat Sasol IPK (isoparaffinic kerosene) or in Sasol IPK doped individually with an organic compound at 8% by volume. Of the aromatic compounds tested, ethylbenzene and indane swelled o-ring seals most effectively, with volume swell percent values of 3.1 ± 0.2% and 2.8 ± 0.1%, respectively. In comparison, the approved aviation fuel Jet A/HEFA has volume swell percent value of 2.2 ± 0.2%. Alkylbenzenes with a smaller number of alkyl groups, less branching in the alkyl groups, and shorter alkyl chains caused greater swelling and greater decrease in the tensile strength for o-ring seals. Naphthene-containing aromatic compounds ( i.e., indane and tetralin) swelled o-ring seals more effectively than alkylbenzenes with the same number of carbons ( i.e., n -propylbenzene and n -butylbenzene). Therefore, steric hindrance seems to have an important impact on the ability of these compounds to swell o-rings. Nonaromatic unsaturated hydrocarbons, such as cyclohexene, were also found to swell o-ring seals to some extent. On the other hand, saturated hydrocarbons, such as cyclohexane, contributed to minimum or no swelling. Tensile strengths of intact o-rings were measured using an MTS Insight Electromechanical Testing Instrument. Aromatic compounds that facilitated greater swelling of o-ring seals also caused greater decrease in the tensile strength. For example, ethylbenzene and sec -butylbenzene, with volume swell percent values of 3.1 ± 0.2% and 0.9 ± 0.1%, respectively, reduced the o-ring tensile strength from 15.4 MPa to 13.6 MPa and 14.9 MPa, respectively. Additional experiments demonstrated that volume swell and tensile strength of o-ring seals are reversible properties. Hence, a decrease in tensile strength for o-ring seals does not imply irreversible damage. Overall, the extent of volume swelling and the lowering of tensile strength for o-ring seals was found to depend on the exact chemical structure of the organic compound.